El diseño como estrategia enfocada en material de refuerzo en casa para niños con trastorno por déficit de atención e hiperactividad. caso de estudio: centro psicopedagógico integral Sullivan de la ciudad de Ibarra - Erazo Rojas, Hillary (2024)
This thesis project arises from an often-overlooked issue in the learning development of children with ADHD, who lack appropriate materials to support their learning process at home. As a result, they tend to encounter general life problems from an early age. The aim of this project is to design reinforcement materials for home use that can help children with ADHD develop their cognitive functions and improve their attention through specific activities. The project is grounded in user-centered design, which, as the name suggests, is based on the requirements provided by the users themselves in this case, the target audience to create high-quality materials. During the diagnostic phase, interviews with experts and parents were conducted, while observation sheets were used for the children. This approach provided the necessary information to develop prototypes and outline the requirements for various proposals. One proposal was selected through evaluation sheets assessed by graphic design expert, health specialists, and parents. Finally, once the proposal was selected, it was validated to ensure it met the children's needs, aiding in the development of their cognitive functions and memory while maintaining the learning already achieved in the psychopedagogical center.